Mechanistic Study of Adsorption of Acid Orange-7 over Aluminum Oxide Nanoparticles. (14th January 2013) - Khosla, Ekta; Kaur, Satindar; Dave, Pragnesh N.
Abstract : The adsorption behavior of acid orange-7 (AO-7) on aluminum oxide nanoparticles (ANP) generated by sol-gel method has been investigated to understand the physicochemical process involved and to explore the potential use of nano particles in textile effluent treatment and management. The results revealed that ANP can remove AO-7 dye up to 97.6 mg/g at 303 K. The adsorption process is found to be pH dependent and the optimum pH obtained is 2.0. The equilibrium was established in 1 h. Langmuir, Freundlich, and Temkin Isotherm models were applied on the system. Scanning electron microscopic analysis reveals eye-catching nanoporous morphology of the material. The results of FTIR spectroscopy reveal that the process is electrostatic complexation mechanism driven. XRD studies revealed nanocrystalline structure of ANP. BET surface area measurement suggests high pore volume and surface area of adsorbent. The kinetic measurements suggest pseudo-second-order kinetic processes. The thermodynamic measurements suggest that all processes are endothermic accompanied with negative Δ G ° and positive Δ S °, Δ H °.